2009
DOI: 10.1038/gt.2009.48
|View full text |Cite
|
Sign up to set email alerts
|

Excision repair cross-complementing 1 expression protects against ischemic injury following middle cerebral artery occlusion in the rat brain

Abstract: To study the effects of excision repair cross-complementing 1 (ERCC1) on the pathophysiological process of brain ischemia, we examined the changes in ERCC1 expression, as well as the functional significance of ERCC1 in the rat brain following middle cerebral artery occlusion (MCAO). The results were as follows: (1) ERCC1 immunopositive cells were widely distributed in various brain regions. ERCC1 expression was localized to the nuclei of neurons and astrocytes. (2) ERCC1 expression, as determined by western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…This result was supported by a recent study that knockdown of ERCC1 expression exhibited an increasing infarct volume in the ischemic rat brain 12 and the report that ERCC1-deficient mice showed increased vascular stiffness and vascular dysfunction 13 . Therefore, combined with the association of SNP rs11615 with ERCC1 expression, we speculated that SNP rs11615 might accelerate the progress of coronary artery atherosclerosis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This result was supported by a recent study that knockdown of ERCC1 expression exhibited an increasing infarct volume in the ischemic rat brain 12 and the report that ERCC1-deficient mice showed increased vascular stiffness and vascular dysfunction 13 . Therefore, combined with the association of SNP rs11615 with ERCC1 expression, we speculated that SNP rs11615 might accelerate the progress of coronary artery atherosclerosis.…”
Section: Discussionsupporting
confidence: 60%
“…ERCC1 is mainly responsible for making incision at the 5′ terminus of DNA lesions by forming a structure-specific endonuclease complex with xeroderma pigmentosum complementation group F (XPF) and may contribute to positioning the nuclease complex at the lesion site by interacting with Xeroderma pigmentosum complementation group A (XPA) 9 . Besides evidence of molecular studies, in animal model studies, the knockdown and overexpression of ERCC1 was related highly to the increase and decrease of infarct volume in the ischemic brain respectively 12 . Mice with ERCC1 deficiency showed vascular dysfunctions, including elevated blood pressure and increased vascular stiffness 13 and also led to elevated serum cholesterol level and the expression change of genes involved in metabolism of cholesterol, which have been considered as traditional risk factors for CAD 14, 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The expression of ERCC1, the rate-limiting component of NER, increases in the ipsilateral cortex and striatum 3–14 days after middle cerebral artery occlusion. Knocking out ERCC1 expression by injecting antisense plasmids increases DNA damage in neurons and promotes infarct sizes after stroke (He et al, 2009). These findings support the view that coordinated DNA repair is essential to complete ischemic recovery.…”
Section: Endogenous Dna Repair Mechanisms After Ischemic Strokementioning
confidence: 99%
“…It was then demonstrated that preischemic treatment of adenovirus-APE diminished the nuclear accumulation of AP site lesions and 8-OHdG, and significantly decreased TUNEL-positive cells and infarct volume after ischemia=reperfusion injury (41). Another study showed that ERCC1 overexpression, by injection of the expression plasmids into the rat brain, significantly reduced the accumulation of DNA-damaged neurons and ischemic cell death after MCAO (31). Given the relatively acute nature of cell death after stroke and the small time window of opportunity for stroke treatment, gene delivery, which needs relatively long time to take effect, may not be a legitimate therapeutic strategy for ischemic stroke.…”
Section: Regulation Of Ber In the Ischemic Brainmentioning
confidence: 98%
“…Overexpression of ERCC1, by injection of expression plasmids, significantly reduced the accumulation of DNA-damaged neurons and ischemic injury. In contrast, reduced endogenous ERCC1 levels, produced by specific antisense, increased DNA damage accumulation and ischemic brain damage following middle cerebral artery occlusion (MCAO), a transient focal cerebral ischemia model (31).…”
Section: Dna Excision Repairmentioning
confidence: 99%